Management of Inclusive Education in Primary Schools - Aishah, Aishah; Sa’ud, Udin Syaefudin; Meirawan, Danny; Nurdin, Diding (Universitas Nahdlatul Ulama Blitar, 2025)
This study aims to analyze the management of inclusive education at the primary school level in Banda Aceh city. The study was conducted in three primary schools, namely SD 20, SD 25 and SD 56 Banda Aceh, using descriptive qualitative methods. Data were collected through observation, in-depth interviews and documentation studies. The results showed that the three schools had implemented inclusive education but with varying levels of readiness and implementation. The management aspects studied included planning, organizing, implementing and evaluating the inclusion program. It was found that factors such as teacher competence, infrastructure, parental support and school policies play an important role in the successful management of inclusive education. The main challenges faced include limited human resources trained in special education, lack of accessible facilities and social stigma towards children with special needs. This study recommends improving teacher training, providing adequate facilities and strengthening collaboration between schools, parents and communities to optimize inclusive education management in primary schools.